2020
DOI: 10.1111/jcal.12470
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing design thinking in instructional technology students

Abstract: There is growing demand in our society to cultivate creativity and foster innovation. Design thinking has been successfully practiced as an educational framework for supporting innovation in educational and work contexts. However, research on design thinking education that facilitates the acquisition of knowledge related to design process and practices is extremely limited, particularly in educational contexts. This pre-/posttest mixed methods study examined blogging as an instructional approach for supporting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…(13) C. Ideate (Ide): which consists of moving from problem formulation to problem solving, focuses on coming up with ideas or using ideas as the foundation for developing prototype designs. (14) D. Prototype (Prototype): referred to as the initial design of a product to be manufactured, is created in order to identify early mistakes and discover new opportunities. The first design created will be put to the test on users in its application to get the right input and reactions to improve the design.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…(13) C. Ideate (Ide): which consists of moving from problem formulation to problem solving, focuses on coming up with ideas or using ideas as the foundation for developing prototype designs. (14) D. Prototype (Prototype): referred to as the initial design of a product to be manufactured, is created in order to identify early mistakes and discover new opportunities. The first design created will be put to the test on users in its application to get the right input and reactions to improve the design.…”
Section: Methodsmentioning
confidence: 99%
“…The first design created will be put to the test on users in its application to get the right input and reactions to improve the design. (14) E. Test: Test or testing, is the process of gathering feedback from various final designs developed earlier in the prototype process. Despite being the final stage, this procedure has a life cycle that allows for looping and returning to the initial design stage in the event of failure.…”
Section: Methodsmentioning
confidence: 99%
“…Another study (Farrar, 2020) also showed that integrating design thinking into biomedical instrumentation projects could boost students' perception of learning. Through an online instructional technology platform, Novak and Mulvey (2020) found that, students preferred using design thinking rather than their creative thinking proper.…”
Section: Design Thinkingmentioning
confidence: 99%
“…Facebook was used by middle school students to write poems (Widodo et al, 2016). Blogs were used by students to write reflections on their design thinking process (Hargrove, 2013;Novak & Mulvey, 2020), and podcasts were recorded by students to capture self-reflections within music teacher education (Bolden & Nahachewsky, 2015). Glogster and Prezi were used to develop posters and presentations, respectively (Magnuson, 2013).…”
Section: What Students Did With Social Mediamentioning
confidence: 99%